2018
DOI: 10.3389/fimmu.2018.02697
|View full text |Cite
|
Sign up to set email alerts
|

Specific MHC-I Peptides Are Induced Using PROTACs

Abstract: Peptides presented by the class-I major histocompatibility complex (MHC-I) are important targets for immunotherapy. The identification of these peptide targets greatly facilitates the generation of T-cell-based therapeutics. Herein, we report the capability of proteolysis targeting chimera (PROTAC) compounds to induce the presentation of specific MHC class-I peptides derived from endogenous cellular proteins. Using LC-MS/MS, we identified several BET-derived MHC-I peptides induced by treatment with three BET-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 47 publications
7
34
0
Order By: Relevance
“…IFN-γ-induced pMHC alterations are distinct from palbociclib. Previous work has demonstrated that CDK4/6 inhibition stimulates IFN signaling, augmenting antigen presentation levels 15 . We also observed upregulation of IFN-γ response genes with low-dose palbociclib treatment, as well as increased expression of genes relating to antigen presentation (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IFN-γ-induced pMHC alterations are distinct from palbociclib. Previous work has demonstrated that CDK4/6 inhibition stimulates IFN signaling, augmenting antigen presentation levels 15 . We also observed upregulation of IFN-γ response genes with low-dose palbociclib treatment, as well as increased expression of genes relating to antigen presentation (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Traditional data-dependent acquisition (DDA) methods to profile pMHC repertoires using mass spectrometry (MS) are well documented [10][11][12] , but quantitative methods have critical limitations. Specifically, most common relative quantification pMHC methods lack a normalization strategy to account for variations in sample input and processing [13][14][15][16][17][18] . Peptide losses during processing vary across peptide sequences, concentrations, and samples, underscoring the need for normalization 19,20 .…”
mentioning
confidence: 99%
“…This suggests that PROTAC-mediated ubiquitination of the viral protein could stimulate the presentation of viral peptides to MHC-I and favor the development of host T-cell therapeutic activity against the viral protein. In fact, this capability has already been reported for PORTACs [4] . These findings mechanistically imply that by leveraging the ubiquitin proteasome system, antiviral PROTACs have the potential of achieving a dual function: 1) degradation of the viral target protein ( Fig.…”
Section: Development Of Protacs To Target Sars-cov-2mentioning
confidence: 72%
“…The ternary complex forms when the PROTAC engages both intended targets, the POI and E3 ligase. This binding activity brings the two proteins together and engages them with PROTAC-mediated protein-protein-interactions [4] . For the ternary complex to be productive, the protein interface must have the following structural requirements or features: 1) minimization of PPIs that cause steric hinderance or electrostatic clashes along the newly formed protein interface 5 , 6 ; 2) maximization of PPIs that promote structural complementarity at the new protein interface 5 , 6 ; and 3) recruitment of the adequate E3 ligase in a proper binding orientation that facilitates target POI ubiquitination [7] .…”
Section: Ternary Complex Requirements Determine Protac Productivitymentioning
confidence: 99%
“…However, a recent study identified the “side effects” of PROTAC in degrading target proteins, such as the emergence of class I major histocompatibility complex peptides during PROTAC‐mediated BET degradation. [ 153 ] In addition, acquired resistance to PROTACs was confirmed in different cells, limiting the clinical application of PROTAC. [ 154 ]…”
Section: Strategies For Selective Protein Degradationmentioning
confidence: 99%